EVALUATION OF THE IMPLEMENTATION OF EIT-4-BPSD: THE MEASUREMENT OF CARE PLANS. (11th November 2018) - Kolanowski, A M; Boltz, M; Van Haitsma, K; Behrens, L; Eshraghi, K J
Abstract: One way to improve person-centered approaches for Behavioral and Psychological Symptoms of Dementia (BPSD) is through care planning. Therefore, we developed and tested the Care Plan Checklist for Evidence of Person-Centered Approaches for BPSD. A total of 137 residents from 14 settings were recruited and the Cornell Scale for Depression in Dementia (CSDD), Resistiveness to Care scale, and Cohen-Mansfield Agitation Inventory (CMAI) were completed. There was evidence of internal consistency (Cronbach alpha .96), inter-rater reliability(r= 0.93), validity based on Rasch analysis and item fit, and a significant relationship between the Care Plan Checklist for Evidence of Person-Centered Approaches for BPSD and the CSDD (r=0.38, p<.001) and CMAI (r=0.44, p<.001). There were 78 care plans so low in evidence of using appropriate interventions that they could not be differentiated. Items should be added to better differentiate those low on the Checklist for Evidence of Person-Centered Approaches for BPSD.